The size of government - António Afonso; Ludger Schuknecht; Vito Tanzi (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We discuss and provide an overview of the size and role of the government, notably in terms of what the government "should" do, how the government could spend and intervene in the economy, how much governments spend and what they spend their money on. This is done from a historical perspective and also in a stylized way via assessing total expenditure, the composition of public expenditure for advanced, emerging and developing countries.
Keywords: B00; E62; H11; H50; H62; 330; public spending; size of government; expenditure composition; public sector efficiency